2005
DOI: 10.1128/jcm.43.2.796-801.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of Anaplasma phagocytophilum Infecting Dogs in Western Washington State

Abstract: Eight dogs from western Washington State suspected of being infected with Anaplasma phagocytophilum because of the finding of morulae in peripheral blood neutrophils were studied for determination of the etiologic agent of disease. All cases were diagnosed between April 2003 and April 2004. Six of the eight dogs had no travel history during the 6 months prior to presentation. Two dogs had traveled within the Northwest United States and Canada. Fever, lethargy, and anorexia were the most common clinical signs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
130
2
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(145 citation statements)
references
References 30 publications
5
130
2
6
Order By: Relevance
“…Other authors also reported the detection of specific IgG antibodies by IFA from 2 weeks up to more than six months after infection in dogs suffering from anaplasmosis (Kirtz et al, 2000(Kirtz et al, , 2005Poitout et al, 2005). To the author's knowledge this is the first confirmed case of canine anaplasmosis caused by A. phagocytophilum to be reported in the Czech Republic, where the infection was already suspected (Huml et al, 1996).…”
Section: Discussionmentioning
confidence: 84%
“…Other authors also reported the detection of specific IgG antibodies by IFA from 2 weeks up to more than six months after infection in dogs suffering from anaplasmosis (Kirtz et al, 2000(Kirtz et al, , 2005Poitout et al, 2005). To the author's knowledge this is the first confirmed case of canine anaplasmosis caused by A. phagocytophilum to be reported in the Czech Republic, where the infection was already suspected (Huml et al, 1996).…”
Section: Discussionmentioning
confidence: 84%
“…scapularis enzootic cycle. Distinct variants not found in humans have been isolated from deer, other ruminants, horses, dogs, and cats, suggesting only a subset of A. phagocytophilum variants cause disease in humans (Lappin et al 2004;Lester et al 2005;Parola et al 2005a;Poitout et al 2005;Morissette et al 2009). More than one strain may be present in a region, and the relative proportion of each strain may vary regionally (Krakowetz et al 2014).…”
Section: Human Granulocytic Anaplasmosis (Hga)mentioning
confidence: 99%
“…The agent has been recognised for some years as a pathogen of veterinary and medical importance. The bacterium is transmitted by ixodid ticks and infects a wide range of species including domesticated ruminants (Gordon et al, 1932), equids (de la Fuente et al, 2005a), cats (Tarello, 2005), dogs (Poitout et al, 2005), wild animals (Skarphédinsson et al, 2005) and humans (Chen et al, 1994;Petrovec et al, 1997). In the United States the principal vectors are Ixodes scapularis and I. pacificus (Dumler, 1997), while in Europe the main exophilic tick vectors are I. ricinus and I. trianguliceps (Ogden et al, 1998).…”
mentioning
confidence: 99%